Strategy-proof mechanism design with non-quasilinear preferences: Ex-post revenue maximization for an arbitrary number of objects - Ryosuke Sakai; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2020)
We consider the multi-object allocation problem with monetary transfers where each agent obtains at most one object (unit-demand). We focus on allocation rules satisfying individual rationality, non-waste fulness, equal treatment of equals, and strategy-proofness. Extending the result of Kazumura et al. (2020B), we show that for an arbitrary number of agents and objects, the minimum price Walrasian is the unique ex-post revenue maximizing rule among the rules satisfying no subsidy in addition to the four properties, and that no subsidy in this result can be replaced by no bankruptcy on the positive income effect domain.
Keywords: D82; D47; D63; 330; Multi-object allocation problem; Strategy-proofness; Ex-post revenue maximization; Minimum price Walrasian rule; Non-quasi-linear preference; Equal treatment of equals; Non-waste fulness